Adab Murid Dalam Kitab Taysir Al-Khalaq Karya Hhafidh Hasan Al-Mas’udi Dan Relevansinya Dengan Pendidikan Sekarang - Nilna Zulfatan Nabila; Ahmad Zuhdi; Ngatoillah Linnaja (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
Adab is a behavior that is considered good and this kindness is carried out continuously which makes it a habit in daily life. In fact, the ethical behavior of students today is very concerning, this is certainly influenced by the lack of understanding of the Qur'an and the book. This study aims to: 1) know the existence of disciples in the book of Taysir al-Khalaq; 2) knowing the existence of disciples in the book of Taysir al-Khalaq and its relevance to education today. This research uses a qualitative research approach where the type of research is library research. The results of this study show that: 1) the discipleship of Taysir al-Khalaq is divided into three: towards himself, towards his teacher and towards his brother. In addition, a student must also have good behavior, namely: tawadhu', understanding the rules of association in Islam, and brotherhood in Islam. 2) the relevance of the book of Taysir al-Khalaq to Islamic education today is very sustainable, because both in terms of material and content in the book, the value in moral education and the purpose of Islamic education in Indonesia is very suitable for use by Islamic educational institutions. Especially in non-formal educational institutions, especially in the cultivation of ethics and morality among students. So that the creation of an Islamic generation that is in accordance with the purpose of Islamic education.